2020 22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe) 2020
DOI: 10.23919/epe20ecceeurope43536.2020.9215865
|View full text |Cite
|
Sign up to set email alerts
|

Gate stresses and threshold voltage instability in normally-OFF GaN HEMTs

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This stress relatively biases the gate terminal of the GaN HEMT positively that might lead the increase of the trap density in the interfaces between layers under gate oxide layer and hetero-interfaces. These traps can cause the decrease of the threshold voltage of the GaN HEMT in cascode structure by reason of positive charges are injected into the heterointerface where 2DEG is formed, from the gate [17]. This threshold voltage decrease can lead to increase of the drain current of the whole cascode devices.…”
Section: B Variety Of the Stress Levels And Period On Drain Terminalmentioning
confidence: 99%
“…This stress relatively biases the gate terminal of the GaN HEMT positively that might lead the increase of the trap density in the interfaces between layers under gate oxide layer and hetero-interfaces. These traps can cause the decrease of the threshold voltage of the GaN HEMT in cascode structure by reason of positive charges are injected into the heterointerface where 2DEG is formed, from the gate [17]. This threshold voltage decrease can lead to increase of the drain current of the whole cascode devices.…”
Section: B Variety Of the Stress Levels And Period On Drain Terminalmentioning
confidence: 99%
“…The results showed that the polarity of the VTH shift depended on the leakage currents of the Schottky contact. Measurements of VTH instability using the third quadrant forward voltage as a technique were introduced in [17,18]. The measurement results showed an initial positive VTH shift for positive VGS stress at high voltages however as the recovery time was increased, the VTH shift became negative.…”
Section: Introductionmentioning
confidence: 99%